Smoking Relapse and Type 2 Diabetes Mellitus–Related Emergency Department Visits Among Senior Patients with Diabetes - Kao, Yu-Hsiang (Prev Chronic Dis, 2019)
INTRODUCTION: Quitting smoking has been proven to benefit smokers with diabetes. However, among older patients with diabetes, the evidence regarding an association between smoking status and the risk of type 2 diabetes mellitus–related emergency department (ED) visits has not been well investigated. METHODS: A retrospective cohort study was performed by using the Louisiana State University Health Care Services Division electronic health records from 2009 to 2011. Patients aged 65 years or older with type 2 diabetes and smoking status recorded at least twice in 2010 were selected. Selected patients with diabetes were classified into nonsmokers, former smokers, continuing smokers, and relapsed smokers. Cox proportional hazards regression models were used to estimate the adjusted hazard ratio (aHR) of 1-year type 2 diabetes–related ED visits for each group compared with nonsmokers. RESULTS: There were 174 (8.2%) continuing smokers and 77 (3.6%) relapsed smokers in 2,114 patients with diabetes who were studied. Rates of type 2 diabetes–related ED visits were highest in relapsed smokers (28.6%). Compared with nonsmokers, relapsed smokers had a significantly higher risk of type 2 diabetes–related ED visits (aHR = 1.62; 95% confidence interval [CI], 1.04–2.50). After stratifying by sex, a significantly increased risk of type 2 diabetes–related ED visits was shown only in male relapsed smokers (aHR = 2.05; 95% CI, 1.13–3.71) and female continuing smokers (aHR = 1.65; 95% CI, 1.10–2.47) compared with nonsmokers. CONCLUSION: Older men with diabetes who were relapsed smokers had a higher risk of type 2 diabetes–related ED visits. Future research and clinical practice should focus on these patients and create more effective interventions for smoking cessation and diabetes management.